Tahlil al-Qiyam al-Akhlaqiyyah fi Asy’ar Qashr al-Malik Banggai li Habib Aydarus: Dirasah Simiya’iyyah ʻInda Michael Riffatere/ Analysis of Moral Values in the Poem Qashr al-Malik Banggai by Habib Idrus: A Semiotic Study by Michael Riffatere - Qadhil Amin Sahupala; Muhsin Ahmad; Rosmah Tami (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
This study examines the moral values in Habib Aidarus bin Salem Al-Jufri's poem "Qashr al-Malik Banggai" using Michel Riffaterre's semiotic theory. Through library research analyzing primary and secondary sources, the poem reveals profound spiritual and ethical messages. It promotes virtues like tolerance, honesty, loyalty, and gratitude while condemning materialism and hypocrisy, asserting that knowledge and righteous deeds are life's only lasting virtues. The poem also emphasizes trust in God, repentance, and acceptance of divine will, contrasting worldly transience with the hereafter's permanence. Rich in literary devices metaphors, paradoxes, and symbolism, the poem contains 36 instances of indirect expression. It frames an eternal struggle between good and evil, centering on a core motif: "Knowledge is an adornment and the greatest good or is it wealth?" This unfolds into three dimensions: (1) the immortality of knowledge, (2) critique of materialism, and (3) reinforcement of religious teachings. The hypogram splits into two layers: a realistic layer addressing the poet's rebuttal of accusations, and an interpretive layer linking the text to the Quran, Hadith, and other poets' works.هدف هذه الدراسة إلى تحليل القيم الأخلاقية في أشعار "قصر الملك بنقاي" للحبيب عيدروس بن سالم الجفري باستخدام النظرية السيميائية لميشال ريفاتير. اعتمد البحث على المنهج المكتبي من خلال تحليل المصادر الأولية والثانوية، حيث كشفت القصيدة عن رسائل روحية وأخلاقية عميقة. تؤكد القصيدة على تعزيز القيم النبيلة مثل التسامح والصدق والوفاء والشكر، بينما تنتقد المادية والنفاق، مؤكدة أن العلم والعمل الصالح هما الفضيلتان الدائمتان في الحياة. كما تركز القصيدة على أهمية التوكل على الله والتوبة والقبول بالقدر الإلهي، مع المقارنة بين زوال الدنيا وخلود الآخرة. تزخر القصيدة بالأساليب الأدبية من استعارات ومفارقات ورموز، حيث تحتوي على 36 حالة من التعبير غير المباشر. تصور القصيدة الصراع الأبدي بين الخير والشر، مركزة على الفكرة المحورية: "العلم زينة والخير الأعظم - أم هو المال" والتي تتطور إلى ثلاثة أبعاد: (1) خلود العلم، (2) نقد المادية، و(3) تعزيز التعاليم الدينية. ينقسم الهيبوجرام إلى طبقتين: طبقة واقعية تتناول رد الشاعر على الاتهامات الموجهة إليه، وطبقة تفسيرية تربط النص بالقرآن الكريم والحديث النبوي وأعمال الشعراء الآخرين.